2010
DOI: 10.1186/1471-2407-10-267
|View full text |Cite
|
Sign up to set email alerts
|

The optimal number of lymph nodes examined in stage II colorectal cancer and its impact of on outcomes

Abstract: BackgroundLymph node status is the most important prognostic factor for colorectal cancer. The number of lymph nodes that should be histologically examined has been controversial. The aims of this study were to assess the impact of the number of lymph nodes examined on survival of patients with stage II colorectal cancer and to determine the optimal number of lymph nodes that should be examined.MethodsThe study included 664 patients who underwent resection for stage II colorectal cancer. The clinical and histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 21 publications
3
40
1
Order By: Relevance
“…Hoenberger considered the lymph node harvest as a surrogate marker of surgical quality reporting a significant difference in survival between node-positive and node-negative patients with a cutoff point of 29 lymph nodes examined [123]. Similar results were reported by Choi with a significant difference in survival when a minimum of 21 nodes were examined; above this number there was no differences [124]. Although there is no consensus on what should be the cut-off point, it makes sense to conclude that the more lymph nodes are retrieved and examined the better will be the quality of care [125].…”
Section: Lymph Node Harvestingsupporting
confidence: 81%
“…Hoenberger considered the lymph node harvest as a surrogate marker of surgical quality reporting a significant difference in survival between node-positive and node-negative patients with a cutoff point of 29 lymph nodes examined [123]. Similar results were reported by Choi with a significant difference in survival when a minimum of 21 nodes were examined; above this number there was no differences [124]. Although there is no consensus on what should be the cut-off point, it makes sense to conclude that the more lymph nodes are retrieved and examined the better will be the quality of care [125].…”
Section: Lymph Node Harvestingsupporting
confidence: 81%
“…In the UK, the Royal College of pathologists recommends examining a minimum of 12 nodes. Some published studies recommend higher number [25]. …”
Section: Lymph Node Involvementmentioning
confidence: 99%
“…In addition, if fewer than 12 lymph nodes were found after careful gross examination, it is suggested that additional techniques that aid in the macroscopic identification of lymph node, such as fat clearing, be considered. Likewise, examination of both halves of each node and preparation of more than one tissue level per paraffin block of nodes improves detection of metastatic disease [25]. …”
Section: Lymph Node Involvementmentioning
confidence: 99%
“…Actually, other reports recommended that more lymph nodes should be examined to ensure proper staging [5,6]. However, it is time-consuming and impractical to obtain more lymph nodes.…”
Section: Introductionmentioning
confidence: 99%